Oxygen saturation ranges for healthy newborns within 24 hours at 1800 m. Issue 3 (2nd February 2017) - Morgan, Melissa C; Maina, Beth; Waiyego, Mary; Mutinda, Catherine; Aluvaala, Jalemba; Maina, Michuki; English, Mike
Abstract : There are minimal data to define normal oxygen saturation (SpO2 ) levels for infants within the first 24 hours of life and even fewer data generalisable to the 7% of the global population that resides at an altitude of >1500 m. The aim of this study was to establish the reference range for SpO2 in healthy term and preterm neonates within 24 hours in Nairobi, Kenya, located at 1800 m. A random sample of clinically well infants had SpO2 measured once in the first 24 hours. A total of 555 infants were enrolled. The 5th–95th percentile range for preductal and postductal SpO2 was 89%–97% for the term and normal birthweight groups, and 90%–98% for the preterm and low birthweight (LBW) groups. This may suggest that 89% and 97% are reasonable SpO2 bounds for well term, preterm and LBW infants within 24 hours at an altitude of 1800 m.